Ralph Compton Straight to the Noose. - Compton, Ralph (Signet, 2015)
When he suffers a major loss at the tables on the Delta Jack riverboat, professional gambler Abner Mason has one night to raise the funds to pay off his debt to the most powerful man on the ship.